Experiencias de trabajo inter y transdisciplinario: espacios de innovación transformativa en una universidad pública en Chile - Ariela Vergara-Jaque; Lady Sthefany Bastías Bastías (INTER DISCIPLINA, 2026)
In response to growing social, cultural, environmental and economic challenges, a public university in Chile implemented an initiative that strengthened research, develop- ment, and innovation (R+D+I) through inter- and transdisciplinary approaches. Through a higher education innovation project, a collaborative academic culture was fostered via the creation of 21 transformative innovation spaces, which benefited from methodological support and specialized training, thanks to partnerships with national and international institutions. These spaces connected the university community with actors from the public and private sectors and civil society, facilitating the co-construction of knowledge with territorial relevance. The initiatives developed were aligned with the Sustainable Development Goals, addressing key areas such as health, sustainability, inclusion, and education. By applying methodologies designed to make research socially relevant, the project promoted reflective processes, active participation, and the transfer of best practices. Although challenges inherent to the formation of diverse teams were identified, the transformative innovation spaces implemented adaptive strategies that strengthened collaborative work and enabled responses to complex and varied issues. This experience laid a solid institutional foundation to drive new models of innovation, positioning the analyzed university as a national and international benchmark in the generation of knowledge with social impact and a strong commitment to regional development.